2020
DOI: 10.1186/s12974-020-01808-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mast cell tryptase attenuates neuroinflammation via PAR-2/p38/NFκB pathway following asphyxial cardiac arrest in rats

Abstract: Background: Cardiac arrest survivors suffer from neurological dysfunction including cognitive impairment. Cerebral mast cells, the key regulators of neuroinflammation contribute to neuroinflammation-associated cognitive dysfunction. Mast cell tryptase was demonstrated to have a proinflammatory effect on microglia via the activation of microglial protease-activated receptor-2 (PAR-2). This study investigated the potential anti-neuroinflammatory effect of mast cell tryptase inhibition and the underlying mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 79 publications
(101 reference statements)
0
7
0
Order By: Relevance
“…]. In cerebral mast cells, Par2 was suggested to activate neuroinflammation through NFkB pathways [ 34. , 35.…”
Section: Introductionmentioning
confidence: 99%
“…]. In cerebral mast cells, Par2 was suggested to activate neuroinflammation through NFkB pathways [ 34. , 35.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxic injury to the CNS leads to local release of leukocyte chemoattractant molecules, 17 making it susceptible to infiltration of neutrophils and secondary inflammatory damage 18,19 . A recent preclinical study in rats demonstrated that the expression of multiple inflammatory mediators is increased in the CNS after cardiac arrest and that pharmacological increasing of these mediators increased seizure activity and worsened neurological outcome, whereas pharmacological reduction of the mediators had an opposite effect 20 …”
Section: Discussionmentioning
confidence: 99%
“…18,19 A recent preclinical study in rats demonstrated that the expression of multiple inflammatory mediators is increased in the CNS after cardiac arrest and that pharmacological increasing of these mediators increased seizure activity and worsened neurological outcome, whereas pharmacological reduction of the mediators had an opposite effect. 20 Multiple studies have shown that elevated levels of inflammatory biomarkers in circulation are associated with poor outcome after cardiac arrest. 3,21,22 This association may depend on case-mix, being stronger in a patient population including more moribund patients 23 compared to a more selected population.…”
Section: Discussionmentioning
confidence: 99%
“…For the pharmacological studies, we used stabilizer of MCs and showed the link between MCs degranulation and neuroinflammation. Tryptase is the major proteins in MCs and has been used as a marker for MCs activation and degranulation ( Oliveira et al, 2013 ; Ocak et al, 2020 ). Our results showed that DSCG treatment decreased the expression of tryptase after early GA exposure.…”
Section: Discussionmentioning
confidence: 99%